Developing and analysing a test case suite for the voltage regulator function block - Ranjkesh, Jehanpour (My University, 2005)
The aim of this thesis was to develop and analyse a test case suite for the voltage regulator function block. This function block is designed for regulating the voltage of power transformers with on-load tap changers in distribution substations. Voltage regulator is a very advanced function block. It has 8 modes and a very wide range of functions. Therefore, testing this function block requires many different test cases to verify the correct operation of the function block. A test case suite was developed for testing the function block. The main idea was to implement this test case suite and find out how efficient the test cases were. Test coverage analysis was the other goal of the thesis. The test case suite was implemented and finally analysed. As a result untested areas of the function block were identified. Also major problems related to the test process were identified as well as proposals for solving them introduced. One of the major problems was lack of good test specification templates, which made implementation of the test cases very difficult. A recommendation, which is using testing techniques to improve the test coverage and the use of standardized templates to control the test process, was introduced. Results showed that since the complete testing is impossible, the only way to ensure the quality of the software is to use systematic testing techniques during different phases of the software development along with standardized testing templates.
Keywords: Software testing; test coverage; voltage regulation.; fi=Tietotekniikka (KTM)|en=Computer Science|; fi=Tietotekniikan koulutusohjelma (DI)|